Facility management - Yousuf, Abu; Syed Radzi, Rahamaddulla (Penerbit UMP, 2017)
This book is intended to be guidance for students or any personnel in desire to understand the foundation of Facilities Management and to enhance their understanding on the importance of Facilities Management. This book covers the basic management concept that is adequately enough to create interest in Facilities Management Career opportunity. The first part comprises of the theoretical element of each critical management area, where as the second part is also covering some financial management part. To make more lively, on every chapter of this module, there is self-test question embedded.